Managing Post-Privatisation Political and Regulatory Risks in Nigeria - a Law and Policy Perspective - Kolo, Abba (2004)
In an effort to revive the ailing economy andjoin the global markets, successive Nigerian governments since 1986, have taken measures that were aimedat liberalising the economy and creating a conducive atmosphere for more private, especially foreign direct investment, long recognised as engines of growth and development and prosperity Among the policy initiatives were: the repeal or amendment of certain laws and regulations that restricted foreign investment, and privatisation of state-owned enterprises. These reform measures have reduced the political risk perception of the country by foreign investors as evidenced in the increased level of foreign participation in the telecommunications, and oil and gas industries. However, with liberalisation and privatisation, new forms of political and regulatory risks emerge that require new management techniques. These risks include possible changes in environmental and social regulations, discriminatory treatment of the private/foreign investor by regulatory agencies through licensing, taxation and enforcement of business laws, control of essential facilities by dominant enterprises, lack of observance of the rule of law and other good governance issues.